Novel first‐year curriculum in high‐value care. (15th January 2019) - Steele, Christopher; Cayea, Danelle; Berk, Justin; Riddell, Rebecca; Kumra, Tina; McGuire, Maura; Pahwa, Amit K
Summary: Background: Most medical schools teach a high‐value care (HVC) curriculum during the clinical years. Currently, there lacks any research demonstrating the effectiveness of the HVC curriculum taught to students in their first year of medical school. Methods: A total of 118 of 466 first‐year medical students at Johns Hopkins School of Medicine between 2013 and 2017 enrolled on an HVC course that provided the initial framework necessary to practice cost‐conscious clinical medicine. The curriculum was evaluated by comparing the performance of students who completed the course with the performance of students without training, through a standardised patient encounter on musculoskeletal back pain and how to approach a patient's request for imaging. Chi‐square testing was used to assess the impact of the course on performance in a standardised patient encounter. Results: Students enrolled on the HVC course were more likely, compared with their counterparts, to assure patients that back pain was a simple strain (48 versus 31%), and were less likely to ask for preceptor help on how to proceed with management (11 versus 29%) [χ 2 (4, n = 466) = 14.28, p = 0.007]. There were no differences between students enrolled on the HVC course who had not yet received training compared with students taking another elective [χ 2 (4, n = 385) = 8.73, p = 0.07]. Discussion: This is the first study to assess the effectiveness of an HVC curriculum for first‐year medical students, and it demonstrates promise that they can acquire some skill sets necessary for cost‐effective practice in a simulated clinical setting. This is the first study to assess the effectiveness of an HVC curriculum for first‐year medical students, and it demonstrates promise that they can acquire some skill sets necessary for cost‐effective practice